Data from: Incidence of influenza A(H3N2) virus infections in Hong Kong in a longitudinal sero-epidemiological study, 2009-2015 - Wei, Vivian W. I.; Wong, Jessica Y. T.; Perera, Ranawaka A. P. M.; Kwok, Kin On; Fang, Vicky J.; Barr, Ian G.; Peiris, J. S. Malik; Riley, Steven; Cowling, Benjamin J. (Dryad, 2019)
Background: Many serologic studies were done during and after the 2009
influenza pandemic, to estimate the cumulative incidence of influenza
A(H1N1)pdm09 virus infections, but there are few comparative estimates of
the incidence of influenza A(H3N2) virus infections during epidemics.
Methods: We conducted a longitudinal serologic study in Hong Kong. We
collected sera annually and tested samples from 2009-13 by HAI against the
A/Perth/16/2009(H3N2) virus, and samples from 2013-15 against the
A/Victoria/361/2011(H3N2) virus using the hemagglutination inhibition
(HAI) assay. We estimated the cumulative incidence of infections based on
4-fold or greater rises in HAI titers in consecutive sera. Results: There
were four major H3N2 epidemics: (1) Aug-Oct 2010; (2) Mar-Jun 2012; (3)
Jul-Oct 2013; and (4) Jun-Jul 2014. Between 514 516 and 614 619 relevant
pairs of sera were available for each epidemic. We estimated that 98%,
2019%, 57% and 7% of the population were infected in each epidemic,
respectively, with higher incidence in children in epidemics 1 and 4.
Conclusions: We estimatedfound that around 5% to 20% of the Hong Kong
population were infectedre-infections in each of the four H3N2 epidemics
that occurred from 2010 through 2014 were rare. The largest H3N2 epidemic
occurred with the lowest level of pre-epidemic immunity.
Read me (data file explanations)Epidemic 1 dataThis data file contains
Epidemic 1 information from the serologic study in Hong
Kong.titer.epi1.csvEpidemic 2 dataThis data file contains Epidemic 2
information from the serologic study in Hong Kong.titer.epi2.csvEpidemic 3
dataThis data file contains Epidemic 3 information from the serologic
study in Hong Kong.titer.epi3.csvEpidemic 4 dataThis data file contains
Epidemic 4 information from the serologic study in Hong
Kong.titer.epi4.csvInfluenza proxy dataThe influenza proxy used in the
analysis.ILILAB.csvTable 1 scriptsR syntax to reproduce results in Table
1.Table1.RTable 2 scriptsR syntax to reproduce results in Table
2.Table2.RFigure 1 scriptsR syntax to reproduce Figure 1.Figure1.RFigure 2
scriptsR syntax to reproduce Figure 2.Figure2.RFigure 3 scriptsR syntax to
reproduce Figure 3.Figure3.RFigure 4 scriptsR syntax to reproduce Figure
4.Figure4.RMain text result scriptsR syntax to reproduce re-infection
results (shown in main text).reinfection.R
Keywords: Influenza; Antibodies; Serology; Serologic study of influenza A(H3N2); Immunity; Vaccination and immunization; Age groups